Modelling Surface Mapping for Engineering Application - Abd Sukur, Nur ‘Amirah (IRC, 2016)
Land surface or topography can helps us to identify proper and safe location for construction site that might affect the cost, time and besides creating the safety related problems. The more safe location of constructions site, the less waste of money and time they can make. Basically, architects or engineers used their basis of their knowledge and experience in making 2D contour maps for analysing the location of buildings.